Molecular mechanism of cleavage of SARS-CoV-2 spike protein by plasma generated RONS - Tan, Shihao; Zhu, Haiwei; Liu, Dawei; Zhang, Song; Chen, Hongxiang (Frontiers in Physics, 2024)
Recently, it's been shown that cold atmospheric pressure plasmas (CAP) effectively inactivate the 2019-nCoV virus. Despite this promising finding, the precise mechanism of this inactivation remains unclear due to the limited number of studies conducted on the subject. Consequently, this paper focuses on the spike protein, a crucial part of the novel coronavirus, and the various reactive oxygen and nitrogen species (RONS) generated by the plasma. The study employs reactive molecular dynamics simulation and ReaxFF potential to explore the reactions between the spike protein molecules and different RONS (including H2O2, OH, O, O3, HOONO, and 1 O2). The findings suggest that when a single RONS interacts with the spike protein, 1 O2 and HOONO have the most potent ability to sever the spike protein. Additionally, the combined effect of long-lived and short-lived RONS presents a more potent decomposition impact.